An AN ANALYSIS OF TRANSLATION ERROR MADE BY STUDENTS AT THE SIXTH SEMESTER OF ENGLISH DEPARTMENT IN IKIP MUHAMMADIYAH MAUMERE - Labira, Darmawan (Udayana Journal of Social Sciences and Humanities; Vol 7 No 2 (2023): Vol 7 No 2 (2023): UJoSSH, September 2023DO - 10.24843/UJoSSH.2023.v07.i02.p01, 2024)
The research aims to describe the kinds of translation errors made by Students at the Sixth Semester of English Department in IKIP Muhammadiyah Maumere. The method used in the research was descriptive qualitative. The subject of the research was the sixth semester students from English Department. The translation text consisting of 1 paragraphs (source texts) and all of it’s’ translations in English (the target texts) were used in the research to find out the translation errors. Then the researchers classified them into 5 kinds of translation errors according to Vilar et al. (2006, p. 698). The results of the research revealed that there were 241 translation errors found in students’ translation. There were translation errors in the form of incorrect word (35, 6%), punctuation (11, 6%), missing word (30, 7 %), word order (15, 3%), and unknown words (6, 6%). In conclusion, the three most prominent error categories made by the students were incorrect word, punctuation and missing word errors.